Optimization and characterization of Sichuan pepper (Zanthoxylum bungeanum Maxim) resin microcapsule encapsulated with β-cyclodextrin. (15th December 2022) - Li, Jianlong; Hou, Xiaoyan; Jiang, Lingyan; Xia, Dong; Chen, Anjun; Li, Shanshan; Li, Qingye; Gu, Xuequan; Mo, Xiaoyan; Zhang, Zhiqing
Abstract: In order to improve the stability of Zanthoxylum bungeanum resin extracted from cakes of fried pepper ( Z. bungeanum Maxim) oil, microcapsules were prepared with β -cyclodextrin ( β -CD) as wall materials using an ultrasonic assisted molecular embedding (UME) method. Effects of the ultrasonic time, ultrasonic power and the core-wall ratio to the encapsulation efficiency (E.E) were investigated. Here, the optimal parameters of resin microencapsulation were determined by response surface methodology (RSM). The maximum E.E (81.94%) was obtained under the optimal parameters where the microcapsules were prepared at the core-wall ratio to be 1:3.47 (w/w) and the ultrasonic treatment was carried out at 240 w for 11.6 min. In addition, the numb grade, moisture content, coliforms and aerobic plate count of resin microcapsules were 6.74, 2.94 g/100 g, 0 MPN∙100 g −1 and 450 CFU g −1, respectively. The sensory evaluation indicated that it was feasible to mask the bitterness and astringent taste of Z. bungeanum resin by preparing microcapsules with an UME method. The resin microcapsules were smooth and continuous surface spherical and ellipsoidal with an average particle size of 2.85 μm. DSC thermogram indicated that the thermal stability of microcapsules was improved compared to the native Z. bungeanum resin. Highlights: Z. bungeanum resin was embedded by ultrasonic-assisted molecular embedding (UME). Resin Microcapsule showed high encapsulation efficiency, small size and good morphology. The bitterness and astringent taste of Z. bungeanum resin was masked by microencapsulation.